Short Communication: Introduction of study domestication of manggabai fish (Glossogobius giuris) in different environment - YUNIARTI KONIYO; JULIANA JULIANA (Biodiversitas Journal of Biological Diversity, 2018)
Koniyo Y, Juliana. 2018. Short Communication: Introduction of study domestication of manggabai fish (Glossogobius giuris) in different environment. Biodiversitas 19: 260-264. Manggabai fish (Glossogobius giuris (Hamilton, 1822) is one of the fish species that have good economic value, so its sustainability needs to be maintained. Manggabai fish population in nature continues to decline; this is due to environmental changes. Environmental changes that occur in nature is very difficult to be controlled so a method is required to preserve the manggabai fish that exist in the natural environment. Domestication is one of the methods used to maintain organisms that lives in a natural environment with an artificial (controlled) environment. This study aims to determine the difference of natural and artificial environment as a basis for conducting domestication on manggabai fish. The research method is an experimental method which is used in the cultivation of fish in natural and artificial environment. Manggabai fish cultivation in the natural environment uses a floating net cage system with volume of 1 m3, while cultivation in a controlled environment uses a pool of 1 m3 of concrete. Manggabai fish uses ± 10 cm of depth of pool with a density of 100 individuals/m3. The study was conducted for 3 months and feeding was only given to cultivation in controlled environment by 20% with a frequency of twice/day. The research variables consist of growth and survival of manggabai fish. The data analysis used descriptive analysis to determine the difference of growth and survival of manggabai fish kept in natural environment and in controlled environment. The results show that there is a difference in the growth and survival of manggabai fish kept in different environments. The highest growth and survival was obtained in the natural environment of KJA by 87%, whereas in the controlled environment, i.e. in the survival pool, it was only 74%. The absolute longest growth and the highest weight growth was obtained in the controlled environment in the pool by 2.07 cm and 4.62 g, whereas in the natural environment in KJA, the growth of the length and the absolute brat of 0.83 cm and 2.33 g. The results showed that the quality of environmental maintenance is a factor that affects the success of manggabai fish domestication.